Psychological Determinants of Continued Obesity One-Year Postbariatric Surgery. Issue 4 (August 2020) - Stapleton, Peta; Spinks, Teagan; Carter, Brett
Objective: Bariatric surgery is an effective treatment for obesity; however, an estimated 20% of patients do not experience significant weight loss postsurgery. This study examined the interaction of potential psychological factors and their mediating effects on the emotional eating of individuals one-year postbariatric surgery. Method: Three-hundred and sixty-six obese individuals (348 females; 95.1%) with a body mass index greater than 30 kg/m 2 ( M  = 39.14; SD  = 7.67) completed the Patient Health Questionnaire, the Brief Cope, the Big-Five Mini-Marker of Personality, and the Three-Factor Eating Questionnaire R-18. Results: The variance accounted for in emotional eating by age and 12 psychological factors were assessed via a four-step hierarchical multiple regression. Avoidant coping and the personality traits of extraversion, agreeableness, and in contrast to that hypothesized, emotional stability were significant predictors of emotional eating. Avoidant coping partially mediated the relationships of extraversion and emotional stability with emotional eating and fully mediated the relationship of agreeableness. Conclusion: Certain personality traits may influence the preferred coping style chosen by individuals who experience continued obesity after bariatric surgery. Additional supports and tailored interventions that are matched with the needs of this population may subsequently be necessary to overcome emotional eating and improve weight loss.